Model of Halal Slaughter Certification Assistance Model for Poultry Slaughterhouse Officers in Supporting Halal Tourism in Batu City - Hardi, Hardi; Sujono, Sujono; Sutanto , A; Baroh, I; Sahara, H (CV. Green Publisher Indonesia, 2024)
The Batu city government is committed to developing halal tourism, especially in meeting the needs of halal food for Muslim tourists. Food that comes from slaughtered animals has a halal critical point that needs to be considered in order to ensure the health and inner peace of the community when consuming meat by providing ASUH meat. Having a certified halal slaughterer and authorized officers to carry out antemortem and postmortem inspections is necessary as a form of consumer protection and implementing halal tourism in Batu City. Training assistance activities were carried out to find the right model for optimizing the competency certification of halal slaughterhouse officers at poultry slaughterhouses in Batu city. This research uses a quantitative descriptive research design and partial least squares (PLS). The results of the research show that before assistance was provided, respondents had low knowledge and abilities regarding the 13 SKKNI competency units so that the halal standards for slaughtered animals were not met, whereas after assistance was provided, respondents met slaughter standards so that the results of their slaughter could be categorized as halal and toyibban and consumers would be protected as halal. Appropriate training and certification is carried out for 7 days, 56 hours of learning and 13 competency units. Effective learning for respondents is at 13.00—17.00 WIB and continued with field practice at the RPA at 19.30—22.00 WIB respectively by applying the one day one competency learning model.